Elements of Cyberspace Management - Jacek OTTO; URBANIAK-MASTALERZ (Communications of International Proceedings, 2021)
The study presents the issues of selected elements of management in cyberspace. The article points to selected problems concerning the management of data security, information, image and human resources in cyberspace. The authors will try to find an answer to the question how to interpret the most important issues related to management in cyberspace. The conclusions from the published research conducted by Ernst & Young on this subject from 2020, based on the available statistics, will constitute a starting point for an assessment in this area and the capability of managers.
Keywords: Management; Cyberspace; Intellectual Property; Protection; Assumptions